Help-seeking behaviour and its impact on patients attending a psychiatry clinic at National Hospital of Sri Lanka - Gomez, D.M.; Gunarathna, C.; Gunarathna, S.; Gnanapragasam, K.; Hanwella, Raveen (Ceylon Medical Journal, 2017)
Background: Mental illness contributes significantly to the global disease burden. There is great diversity in the manner in which mentally ill patients seek help as this is influenced by their beliefs and the opinion of the family-social support unit. The stigma associated with mental illness is a barrier to effective therapy in Sri Lanka where systematic public awareness programmes are minimal. Objective: To study the help-seeking behaviour and its impact on patients attending a psychiatry clinic of the National Hospital of Sri Lanka. Methods: A cross sectional study was carried out among 120 attendees of the psychiatry clinic of the National Hospital of Sri Lanka. Sample was selected using systematic sampling. Data was collected using an interviewer administered questionnaire. Results: More than half the participants sought psychiatric care as their first help-seeking behaviour and found it significantly more useful than non-psychiatric care alternatives. The average time to seek psychiatric care, irrespective of the pathway to care, was less than one month. The recommendation of the family and the social support unit and perceiving that the symptoms were due to a mental illness were the key factors in determining help-seeking behaviour. The average expense on alternative care was zero. There was no significant difference on the impact to employment among those that chose psychiatry care initially from those that did not. Conclusions Our findings suggest that mentally ill patients presenting to a tertiary care hospital in Colombo, are likely to seek psychiatric care early. This is probably due to better recognition and knowledge regarding available treatment.
Keywords: Help-seeking behaviour; patients; MEDICINE::Psychiatry; National Hospital; Sri Lanka